BEE MILK AND ITS IMPORTANCE IN THE FIELD OF PHARMACEUTICS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article talks about the chemical composition of bee milk, its usefulness, the method of obtaining bee milk, studying and taking measures to preserve it.